Women’s News Coverage in Local Mass Media: A Case of Regional Head Election 2018 - Sweinstani, Mouliza K.D (Politika: Jurnal Ilmu Politik, 2022)
The mass media can play a crucial role in election campaigns because it can influence people's points of view of a candidate, including how they responded to women candidates. This paper aims to analyze how the local media portrayed women candidates in the Local Executive Election (Pilkada) 2018 and the factors that drive it. Unlike most previous studies, which focused on women in legislative candidacy and analyzed the national mass media, this study focuses on women's candidacy in the local executive election by observing the local mass media. The author believes that the differences in the electoral system between the legislative election and the local executive one and the differences of the media scop will produce different findings. Using the explanatory sequential mixed method, the author combined the quantitative method followed up with the qualitative one to interpret this study's data. The author took a sample of 140 pieces of news from local mass media during March-23 June 2018, which was chosen by a non-probability sampling method with a quota technique. This study did not reveal any biased coverage toward women candidates due to four factors: the type of election that women participate in; the social-political capital of women candidates; the condition that women's active political participation is not a novelty; and the alignment of media to the more extensive political agenda. Therefore, it can be concluded that the neutrality of the media does not necessarily cause unbiased coverage, yet by the logic of the media, which makes the media are not passive conduits.